Assay of Endogenous 3,5-diiodo-L-thyronine (3,5-T2) and 3,3′-diiodo-L-thyronine (3,3′-T2) in Human Serum: A Feasibility Study - Lorenzini, Leonardo; Nguyen, Nhat Minh; Sacripanti, Ginevra; Serni, Enrico; Borsò, Marco; Saponaro, Federica; Cecchi, Elena; Simoncini, Tommaso; Ghelardoni, Sandra; Zucchi, Riccardo; Saba, Alessandro (Frontiers in Endocrinology, 2019)
3,5-diiodo-L-thyronine (3,5-T2) is an endogenous derivative of thyroid hormone with potential metabolic effects. It has been detected in human blood by immunological methods, but a reliable assay based on mass spectrometry (MS), which is now regarded as the gold standard in clinical chemistry, is not available yet. Therefore, we aimed at developing a novel ad-hoc optimized method to quantitate 3,5-T2 and its isomers by MS in human serum. Serum samples were obtained from 28 healthy subjects. Two ml of serum were deproteinized with acetonitrile and then subjected to an optimized solid phase extraction-based procedure. To lower background noise, the samples were furtherly cleaned by hexane washing and acetonitrile precipitation of residual proteins. 3,5-T2 and its isomers 3,3’-T2 and 3’,5’-T2 were then analyzed by HPLC coupled to tandem MS. Accuracy and precision for T2 assay were 88-104% and 95-97%, respectively. Recovery and matrix effect averaged 78% and +8%, respectively. 3,5-T2 was detected in all samples and its concentration averaged (mean±SEM) 41±5 pg/ml, i.e. 78±9 pmol/l. In the same samples the concentration of 3,3’-T2 averaged 133±15 pg/ml, i.e. 253±29 pmol/l, while 3’,5’-T2 was not detected. 3,5-T2 concentration was significantly related to 3,3’-T2 concentration (r=0.540, P<0.01), while no significant correlation was observed with either T3 or T4 in a subset of patients in which these hormones were assayed. In conclusion, our method is able to quantify 3,5-T2 and 3,3’-T2 in human serum. Their concentrations lie in the subnanomolar range, and a significant correlation was detected between these two metabolites in healthy individuals.